Effect of feeding deoiled mahua (Bassia latifolia) seed cake on the growth performance, digestibility and balance of nutrients in cross‐bred calves during pre‐patent period of Fasciola gigantica infection. Issue 2 (28th July 2014) - Jacob, A. B.; Singh, P.; Verma, A. K.
Summary A study was conducted to assess the growth performance and nutrient utilization of cross‐bred calves serially infected with Fasciola gigantica and/or supplemented with deoiled mahua seed cake (DMSC) during pre‐patent period of infection. Twenty healthy cross‐bred (Holstein Friesian × Haryana) male calves aged 6–7 months with an initial average live weight of 79.6 ± 2.71 kg were divided into four treatment groups (CON, CON‐INF, DMC and DMC‐INF) of five animals each following randomized block design. DMSC was included in the concentrate mixture of DMC and DMC‐INF groups at 100 g/kg level. Animals of groups CON‐INF and DMC‐INF were given an infection of 200 metacercariae (mc) of F. gigantica as serial infection dose of 50 mc twice weekly over a period of 2 weeks. A metabolism trial at 40–49 days post‐infection and growth trial of 145 days duration were conducted. The average daily gain (ADG) and feed conversion ratio (FCR) were significantly (p < 0.05) lower in CON‐INF group as compared to others. The ADG and FCR were significantly (p < 0.05) higher in DMC‐INF as compared to CON‐INF. The intake and digestibility of nutrients were not affected by serial infection with F. gigantica during pre‐patent period. However, significantly (p < 0.001) higher urinary excretion and significantly (p < 0.001) lower nitrogen balance were observed in CON‐INF group as compared to other three groups. The nitrogen balance was significantly (p < 0.001) improved in DMC‐INF group as compared to CON‐INF group. From the results, it may be deduced that the supplementation of deoiled mahua seed cake at 100 g/kg level in the concentrate mixture has improved the growth performance and nitrogen utilization in cross‐bred calves infected with F. gigantica.